Evaluating Catalyst Performance in Synthesizing Hydroxyl-Terminated Polybutadiene by Ring-Opening-Metathesis Polymerization - Su, Gillian A.; Reiter, Paul; Schulz, Michael D. (Synlett, 2023)
Hydroxyl-terminated polybutadiene (HTPB) can be synthesized by ring-opening metathesis polymerization (ROMP) in a one-step process using cyclooctadiene in the presence of a hydroxyl-functionalized chain-transfer agent (CTA). However, previous studies have shown that the presence of primary alcohols can lead to the degradation of some ruthenium catalysts and that the hydroxyl end groups may be converted into aldehydes. Here we compare the performance of five ruthenium-based catalysts — Grubbs first-, second-, and third-generation catalysts (G1, G2, and G3, respectively), Hoveyda–Grubbs Z-selective catalyst (HGZ), and Hoveyda–Grubbs second-generation catalyst (HG2) — in ROMP with a CTA containing primary alcohols. We found that HTPB can be rapidly synthesized in a single step using G3 while avoiding end-group isomerization (2.2% aldehyde formation after full conversion is reached in 5 min). This result suggests that G3 may enable a more effective approach to synthesizing HTPB that avoids protecting groups but still maintains high end-group fidelity.
Keywords: catalyst performance; hydroxyl-terminated polybutadiene; ring-opening metathesis; polymerization